2014
DOI: 10.1149/2.0381412jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hydrophobic Groups on Quaternary Ammonium Additives for Copper Electrodeposition

Abstract: A series of quaternary ammonium compounds with different hydrophobic groups as spacers were synthesized. The influence of the hydrophobic groups on the additives for copper electrodeposition was investigated using a galvanostatic measurement on a RDE electrode. The increase of the length of the alkyl chain within the compounds enhances the suppressing capability. The introduction of a hydroxyl group or a phenyl ring into the hydrophobic groups in the molecular structures reduces the suppressing capacity. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…These potential oscillations are considered to be the repeated construction and destruction of a complex layer between a certain additive and accelerator. 23,39,40 Therefore, this phenomenon that was similarly observed in other injection conditions might be related to the instability of the inhibition layer during the competitive adsorption between Lev 3 and SPS. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…These potential oscillations are considered to be the repeated construction and destruction of a complex layer between a certain additive and accelerator. 23,39,40 Therefore, this phenomenon that was similarly observed in other injection conditions might be related to the instability of the inhibition layer during the competitive adsorption between Lev 3 and SPS. On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Among the additives, levelers play a key role in void-free filling of microvias based on the convection-dependent adsorption behavior, like the position dependency on vias. 2,19,21,22 Recent studies report that the inhibition effect of levelers can be varied by the structure of levelers, such as functional groups, 19,[23][24][25] side chain length, [26][27][28] aromatic rings, 29,30 and counter ions. [31][32][33] Thus, studying the better understanding of the structure-property relationship of additives could assist in understanding the inhibition mechanism of levelers for achieving void-free filling and designing the new levelers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…N,N,N′,N′ ‐Tetramethyldipropylenetriamine (TMBPA) (purity >98%) and N ‐[2‐(2‐dimethylaminoethoxy)ethyl]‐ N ‐methyl‐1,3‐propanediamine (purity >98%) were obtained from Huntsman corporation and Evonik, respectively. N,N′ ‐Bis[3‐(dimethylamino)propyl]urea (purity >97% by GC–MS) was in‐house prepared followed a procedure as described previously with some modification.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, quaternary ammonium compounds (QACs) have the potential to suppress various detrimental morphologies. [9][10][11][12][13][14][15][16] Lan et al chose tetraalkylammonium hydroxides to inhibit the growth of zinc dendrite in alkaline media, and found that the inhibition ability is dependent on the size of the alkyl groups and the concentration of additives. 11 Wang et al used the quaternary ammonium compounds with different functional groups as levelers for copper electrodeposition and concluded that increasing the length of alkyl groups can enhance the inhibition effect on metal deposition.…”
mentioning
confidence: 99%